Geography and history of the frying process - I. D. Morton (Grasas y Aceites)
How far back in time, frying with oil goes, it is difficult to tell. The rules for sacrifice in Leviticus, Chapter 2, the 3rd book in the Old Testament, which is commonly accepted to date from about 600 BC, distinguishes between bread baked in the oven and that cooked «on the griddle» or «in the pan». Roman authors also describe in the first century AD the frying of eggs. Writers in the Middle Ages, Cervantes and Chaucer both describe the cooking in oil. A number of common proverbs deal with frying in one's own grease in the 14th Century. Soyer describes the grid iron as a primitive utensil but with considerable possibilities in the use and variation of the cooking process. We need only to recall that splendid painting in the El Prado of the fried egg which Professor Varela used as a frontispiece for the first Frying of Food Conference in Madrid in 1986. Different types of oils can be used for the frying of food. Variations in the composition of vegetable oils can normally be traced back to climatic effects and the location of the growing plants. We can expect the height above sea level, the daylight hour length, the mean temperature and the genetic make up of the plant, all to have an effect. Cool conditions during seed maturation can increase the linoleic acid content In plants such as Guizotia Abyssinica to almost 85% of the oil. Similar results have been reported for peanuts grown at different latitudes in the United States.